Pengaruh Kepuasan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT Nusatrans Anugerah Makmur - Septiana Elma Sinta; Iswati Iswati; Siti Aisyah; Anis Fitriyasari (JURNAL RISET MANAJEMEN (JURMA), 2024)
Job satisfaction and employee discipline are closely related to employee performance. In accordance with the subject matter raised, namely the effect of job satisfaction and work discipline on performance at PT Nusatrans Anugerah Makmur.the background of this research is that there have been many cases of low job satisfaction and work discipline PT Nusatrans Anugerah Makmur, this has resulted in negative things. Job satisfaction which is considered positive is an increase in performance, loyalty and commitment to the company. the higher the job satisfaction, the better the employee's work discipline. conversely, the lower the job satisfaction, the worse the employee's work discipline. this study aims to determine the effect of job satisfaction and work discipline on employee performance PT Nusatrans Anugerah Makmur. this type of research is associative. The population of this study were all employees at PT Nusatrans Anugerah Makmur and all were sampled. this study uses the census method or saturated sample.The data collection techniques in this study were questionnaires and library data.